Role of DNA Methylation and Adenosine in Ketogenic Diet for Pharmacoresistant Epilepsy: Focus on Epileptogenesis and Associated Comorbidities - Chen, Fan; He, Xinghui; Luan, Guoming; Li, Tianfu (Frontiers in Neurology, 2019)
Epilepsy is a devastating neurological disorder characterized by an enduring predisposition to generate epileptic seizures and by the associated comorbidities such as neurobiologic, cognitive, psychological, and social consequences of this condition. Despite the clinic availability of many new antiepileptic drugs (AEDs) with differing mechanisms of action, more than one-third of patients experience epilepsy that remains uncontrolled. Until now, no AEDs have been proven to halt disease progression or to prevent the development of epilepsy. The ketogenic diet, the high-fat, low-carbohydrate composition is an alternative metabolic therapy for epilepsy, especially for children with refractory epilepsy. Recently clinical and experimental results demonstrate its effectiveness in ameliorating both seizures and comorbidities associated with epilepsy such as cognitive/ psychiatric concerns for the patients with refractory epilepsy. Of importance, ketogenic diet demonstrates to be a promising disease-modifying or partial antiepileptogenesis therapy for epilepsy. The mechanisms of action of ketogenic diet in epilepsy have been revealed recently, such as epigenetic mechanism for increase the adenosine level in the brain and inhibition of DNA methylation; upregulating key bacterial species which synergize to decrease gammaglutamylation of amino acids, increase hippocampal GABA/Glutamate ratios, and, ultimately, prevent seizures; direct inhibition of AMPA receptors (glutamate receptors), and alteration of cell energetics through mitochondrial biogenesis; rescuing the seizure induced abnormal expressions of Scn1a and Scn3a by downregulation of GAPDH expression. In the review, we will focus on the mechanisms of ketogenic diet therapies underlying adenosine system in the prevention of epileptogenesis and disease modification. In addition, we will review the role of ketogenic diet therapy in comorbidities associated epilepsy and the underlying mechanisms of adenosine.